Anti-Caucasian folding of the Kura-South Caspian Hollow (by the example of South Caspian Basin and Cis-Lesser Caucasian trough) - Pogorelova, E.; Abdulla-zada, M. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The South Caspian Basin (SCB) is the deepest submerged sedimentary basin in the World and occupies the entire southerndeep-water part of the Caspian Sea and the Kura and West Turkmenian lowlands adjacent to it from the west and east. The SCBhas the thinnest (6...8 km) consolidated oceanic-type crust and the thickest sedimentary cover (25...30 km). The thickness of thePliocene-Quaternary deposits is 10...12 km. The thickness of the main oil and gas complex – Productive-Red-Colored Strata of the Lower Pliocene is 7 ... 8 km. More than 6 km of volcanic-sedimentary deposits accumulated within the Lesser Caucasian trough at the Mesozoic stage of development. However, in the western part of the trough the translucent pre-Jurassic basement which has a northeastern orientation formed a similar orientation of the overlying deposits. All of the above mentioned events took place under conditions of compression in the north of SCB which were realized at the level of the consolidated crust by subduction, and at the level of the sedimentary cover by structure forming processes. Primary migration passes into the lateral from the submerged zones to the uplifted ones. Deep faults that have formed transverse folding can also serve as migration routes. The submerged predominantly gas-bearing depositional zone of the Productive Strata is represented by folding of both Caucasian and anti-Caucasian strike. Despite the fact that the Kura-South-Caspian depression at the present stage covers the territory from the Dziruly massif in the west to the West Turkmenian depression in the east inclusive as a single negative structural element, in the Mesozoic time as follows from the above it represented two independent areas of subsidence and sediments accumulation in the Transcaucasian microcontinent (western part) and the Greater Caucasian-South Caspian rift basin (eastern part). Therefore, the anti-Caucasian folding of the Kura-South Caspian depression has a different genesis and naturally a different oil and gas potential.
Keywords: oil and gas bearing; oil and gas potentia; folding; Transcaucasian microcontinent; oil and gas potential